Kontrol Lampu Berbasis Voice Command Pada Raspberry PI - Muhammad Irfan Reza; Sabriansyah Rizqika Akbar; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Smart home is a home that provides comfort, safety and convenience to its inhabitants in the operation of every device in every time. Smart home usually consists of some electronic device such as lamps, fans, air-conditioner, etc. One of the smart home control methods currently developing is voice control. Currently there are some voice control technology that is being developed one of them is the voice control system developed by Amazon.. In this research will be implementing Alexa Voice Service on raspberry pi device so that the device can control the lamp to turn off, turn on, change color, set intensity and do scheduling.Voice commands received on the raspberry will be sent to alexa skills kit via alexa voice service that is installed in raspberry, then voice command that has been received in alexa skills kit will be sent to amazon web service lamba to modeled with JSON format so it can be recognized by system. The formatted data will be published to MQTT Broker. System will subscribe the data as a reference action what will to do. The accuracy of the system's success in translating voice commands to turn off and turn on is 95.8%, to change color is 100%, to set the intensity is 93.3%, to do scheduling is 100%.